2023
DOI: 10.1027/0269-8803/a000300
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Interoceptive Accuracy With Risky Decision-Making and Treatment Outcomes in Male Patients With Alcohol Use Disorder

Abstract: Abstract. Lower levels of interoceptive awareness (IA) may be present in individuals with substance use disorder (SUD), and damage to related brain regions caused by substance use may disrupt IA. Disturbance in the bodily feedback system may fail to engage in effective decision-making. This study focused on the premise that interoceptive accuracy (IAc), as the primary construct of IA, is implicated in SUD and that poor IAc is linked to risky decision-making and adversely affects treatment outcomes. Eighty-five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In contrast, Brevers et al (2014) [70] found no significant association between IGT, CGT, or CT performance and the number of cigarettes consumed per day in a combined group of AUD and control participants. Similarly, two studies found no significant correlation between IGT performance and the smoking amount or history of the AUD group [76,99] or the CG [76]. In line with these findings, Loeber et al ( 2009) [52] did not observe a significant correlation between the severity of nicotine dependence and IGT performance, and in the study by Brière et al (2019) [78], no significant correlation was found between IGT performance and the presence of co-addictions.…”
Section: Clinical Characteristicsmentioning
confidence: 76%
See 4 more Smart Citations
“…In contrast, Brevers et al (2014) [70] found no significant association between IGT, CGT, or CT performance and the number of cigarettes consumed per day in a combined group of AUD and control participants. Similarly, two studies found no significant correlation between IGT performance and the smoking amount or history of the AUD group [76,99] or the CG [76]. In line with these findings, Loeber et al ( 2009) [52] did not observe a significant correlation between the severity of nicotine dependence and IGT performance, and in the study by Brière et al (2019) [78], no significant correlation was found between IGT performance and the presence of co-addictions.…”
Section: Clinical Characteristicsmentioning
confidence: 76%
“…In the AUD groups, a higher age was found to correlate significantly with a worse (i.e., riskier) performance on the CGT [83], and with a better (i.e., less risky) performance on the RTT [67] and the EGT [58]. Contrastingly, three studies found no significant correlation between age and IGT performance in the AUD group [76,94,99] or the CG [76]. In combined samples of AUD and control participants, two studies further found no significant correlations between age and IGT [70,82], CFT/LA(G)T [70], and CT performance [70].…”
Section: Demographic Characteristicsmentioning
confidence: 85%
See 3 more Smart Citations